Detection and quantification of the top-seven Shiga toxin-producing Escherichia coli serogroups in feces and on hides of feedlot cattle and whole genome sequence-based analysis of O103 serogroup - Noll, Lance (Kansas State University, 2017)
Cattle are a reservoir for major Shiga toxin-producing Escherichia coli (STEC), which includes STEC O157 and the top six non-O157 serogroups (STEC-6; O26, O45, O103, O111, O121, O145). Collectively known as the STEC-7, these organisms are harbored in the hindgut and shed in the feces of cattle, which can contaminate hides. The de-hiding step during beef cattle processing can introduce fecal contaminants from the hide onto the carcass surface, creating the potential for contaminated beef products. The STEC-7 have been declared by the USDA-Food Safety and Inspection Service as adulterants in ground beef and non-intact beef products, and are monitored during beef cattle processing. However, many of the culture- and PCR-based tests for detection and/or quantification of the STEC, particularly of the STEC-6, are not established or require improvement and also virulence characteristics of STEC strains from cattle have not been fully analyzed. Therefore, the following studies were conducted: 1. Immunomagnetic separation (IMS)-based culture-method for detection of STEC-6 in cattle feces was developed and compared to a PCR-based method; 2. Detection sensitivity of pooled vs. individual IMS beads for isolation STEC-6 from cattle feces was evaluated; 3. Real-time PCR assay, based on the clustered regularly interspaced short palindromic repeat sequence polymorphisms (CRISPR), was developed and validated for serotype-specific detection and quantification of STEC O157:H7 in cattle feces; 4. Virulence gene profiles of bovine enterohemorrhagic (EHEC), enteropathogenic (EPEC) and putative non-pathotype E. coli O103 strains were examined with whole genome sequence (WGS)-based comparative analysis; 5. Prevalence and concentration of STEC-7 of fed-beef, cull beef and cull dairy cattle were determined. The culture and PCR methods detected all six serogroups in samples negative by the other method. Based on noninferiority tests, detection with pooled IMS beads was not inferior to detection with individual beads. Detection limits of the CRISPR-based qPCR assay for cattle feces spiked with pure cultures were 2.1 x 10³ and 2.3 x 10⁰ colony-forming units/g before and after enrichment, respectively. WGS-based analysis of E. coli O103 strains revealed key differences in the virulomes and mobilomes of EHEC, EPEC, and putative non-pathotype strains. The prevalence study revealed that a significantly higher (P < 0.01) proportion of hide samples from fed beef cattle (4.8%) were positive for STEC O157:H7, compared to samples from cull beef (1.6%) or cull dairy (0.2%); the majority of quantifiable STEC O157:H7 from each cattle type was at concentrations between 3 to 4 log CFU/100 cm². These data contribute to a knowledge gap on prevalence and concentration of STEC-7 and surrogate bacteria on cattle hides and carcasses, respectively. Furthermore, the development and refinement of culture- and PCR-based screening assays may lead to increased surveillance of major STEC serogroups, especially if the potential of WGS-based comparative genomics in identifying novel gene targets can be harnessed.
Keywords: Cattle fecesShiga toxin-producing Escherichia coli